The CONSTANS-like 2 Gene Serves as a Pivotal Regulator of Flowering in Hemerocallis - Chunjing Guan; Yike Gao; Ziyi Wang; Qixiang Zhang (Plants)
Hemerocallis spp. exhibit distinct flower opening times, categorized into nocturnal and diurnal types. Previous studies have demonstrated that the circadian clock and CONSTANS (CO) genes play crucial roles in regulating flowering in Hemerocallis. However, the key genes that integrate flowering pathways remain largely unknown. To address this gap, we identified potential homologs of the FLOWERING LOCUS T (FT) gene in Hemerocallis. A yeast one-hybrid assay revealed that HfCOL2 and HfLHY directly bind to the HfFT1 and HfFT2 promoters, thereby activating FT transcription. The expression analysis reveals that HfCOL2 expression rhythms not only display opposing patterns between nocturnal and diurnal opening types of Hemerocallis but also between leaf and flower tissues. The peak expression of HfCOL2 in flowers aligns closely with the respective opening times of diurnally and nocturnally flowering Hemerocallis. The overexpression of HfCOL2 in tobacco plants led to early flowering and prolonged flower longevity. In Hemerocallis, the HfCOL2 gene plays a pivotal role not only in photoperiod-induced flowering but also in the circadian rhythm-mediated regulation of flower opening time. Due to the limited availability of plant materials exhibiting distinct flower opening rhythms, research in this area has been constrained. Identifying the key genes in the flowering pathway of Hemerocallis can facilitate a better understanding of the mechanisms by which plants respond to circadian rhythms.